African Human Rights Law Reports 2005 Edited by African Commission on Human and Peoples' Rights and the Centre for Human Rights, University of Pretoria - Edited by African Commission on Human and Peoples' Rights and the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2007)
African Human Rights Law Reports 2005 Edited by African Commission on Human and Peoples' Rights and the Centre for Human Rights, University of Pretoria 2007 ISSN: 1812-2418 Pages: xxx 244 Print version: Available Electronic version: Free PDF available